IMPLEMENTASI PEMASARAN SYARIAH PADA HOTEL SYARIAH PERSFEKTIF ETIKA BISNIS ISLAM - Apriani, Triana; Ningsih, Surya; Solihin, Asep; Saefuddin, Aep; Rahayu, Wati (Program Studi Ekonomi Syariah, 2025)
Sharia Hotel Marketing is a strategic business that directs the process of creating, offering, and changing value from an initiator to its stakeholders, which in the whole process is in accordance with the contracts and principles of muamalah and its perspective in Islamic business ethics. This article is a type of descriptive qualitative study of case studies that aims to describe the implementation of sharia hotel marketing, while the data used in this study are secondary data, secondary data is data obtained not directly from the source, including from literacy sources, and data from processed primary data collection. The results of this study are that not all sharia hotels market lodging service products and along with other facilities attached to sharia hotels, truly sharia, this is evidenced based on data from rating values and from reviews of hotel guest services that have stayed at various sharia hotels in Bandung City from the Agoda application